Exponential stabilization of thermoelastic system of type II with non-uniform bounded disturbance. Issue 2 (25th January 2018) - Wang, Lei; Feng, Xiao-Yu; Han, Zhong-Jie; Xu, Gen-Qi
Abstract : The boundary stabilization problem of a thermoelastic system of type II with a tip-mass is considered with the assumption that there is an external non-uniform bounded disturbance at the control end. In order to estimate this kind of disturbance, a time-varying high-gain estimator is designed, where the idea of active disturbance rejection control is adopted. Based on the estimate of disturbance, we propose a boundary feedback controller so as to exponentially stabilize this system. Finally, some numerical simulations on the dynamical behavior of the closed-loop system are given.